Militärsiedlungen und Territorialherrschaft in der Antike - Daubner, Frank (2011)
In a series of case studies, the contributions assess the extent to which in the Ancient World control over large territories relied on the settlement of active or retired soldiers. The central question is that of the link between the historical situation of the foundation, those involved, and the location of the settlement on the one hand and, on the other, the strategic importance which can be derived from these factors for the domination of territories on land and sea, roads, frontiers, other towns, a previous population etc.; in other words the connection between spatial conditions and his...